Role of stimulus dose on neuropsychological functioning after electroconvulsive therapy in patients with major depressive disorder - Rummel, Lea; Göke, Katharina; Philipsen, Alexandra; Hurlemann, René; Kiebs, Maximilian (Frontiers in Psychiatry, 2024)
Introduction: Electroconvulsive therapy (ECT) is the most effective treatment for patients suffering from treatment-resistant depression but its use is often limited by the concern for cognitive side effects.This study examines the effect of ECT on autobiographical and verbal memory compared to a healthy control group and the impact of the mean stimulus dose on cognition after ECT.Methods: Autobiographical and verbal memory were assessed in depressed patients and healthy controls before the first and within one week after the last ECT treatment. Neuropsychological testing included the Autobiographical Memory Interview, the Verbal Learning and Memory Test and five tests from the Cambridge Neuropsychological Test Automated Battery. The mean charge delivered across the ECT series and the total number of sessions were examined in relationship to cognitive impairment after ECT using a multiple regression model.Results: Autobiographical memory was significantly impaired after ECT treatment compared to healthy controls. Baseline scores were lower for depressed patients on all cognitive domains. Improvements in performance after ECT were found on tests for executive functions and working memory. Effects of the mean charge delivered on cognitive functioning after ECT were heterogeneous across cognitive domains but significant for verbal retrograde memory.ECT led to autobiographical and verbal memory impairment. The relationship between mean charge delivered and cognitive performance is heterogeneous across different cognitive domains and requires further research. Significant effects of the mean charge delivered were found without a significant difference in cognitive functioning compared to a healthy control group.